Implementasi Sistem Enterprise (ERP) Dalam Perencanaan Produksi Pada Arkem Coffee Cirebon Menggunakan Pendekatan Social Commerce - Luis, Michael Fernando; Tanaamah, Andeka Rocky; Tanaem, Penidas Fiodinggo (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2024)
Arkem Coffee Cirebon is an MSME coffee shop located on Jalan Arya Kemuning, Kesambi District, Cirebon City. The sales process for Arkem Coffee Cirebon is carried out conventionally/offline. The problem of the unavailability of the online sales process requires an information system to overcome this problem, namely by using ERP implementation through social commerce. The ERP implementation method uses a social commerce approach, which is a system created using data and procedures to provide products and services through social media applications. This method was chosen because the owner experienced obstacles in developing products and services. This method was deemed able to overcome these obstacles because he saw that the development of sales through online media was accelerating rapidly and could be easily operated by the coffee shop. This research method uses descriptive research methods, interviews and observations. Designing an overview of online business processes is carried out using the business process re-engineering method. Through the implementation of this information system and design, Arkem Coffee Cirebon can implement online business processes in its business.